"Person" in the Law of Religious [Institutes] - Němec, Damián (Philosophy & canon law, 2021)
The emphasis on the human person and his dignity was significantly applied in the new regulation of the law of consecrated life, which is dealt with in the new Code of Canon Law of 1983 in integrum compared to the previous Code of Canon Law of 1917. This paper describes only some of the changes in the law of religious institutes in the Latin Church.The first section regards mainly the person who has taken religious vows and focuses on the question of religious vows as the basis of religious life. It also discusses confessors viewed as a necessary tool for the renewal of religious life as well as modifications in the concept of poverty as a very important element of religious life. The second section focuses on the government of religious institutes, discussing the strengthened position of internal superiors over external superiors in religious congregations, the strengthened position of the superior of monasteries of nuns, and the extended powers of superiors on release from a religious institute due to illegitimate absence from a religious house.As this is in some cases a very recent legal regulation, the author does not hesitate to express his critical observations.